BYOD data protection survey and advice from ICO (2013)
Presents a report on the survey commissioned by the Information Commissioner's Office (ICO), UK which has shown that many employers appear to have a 'laissez faire' attitude to allowing staff to use their personal laptop, tablet computer or smartphone for work business, which may be placing individual's personal information at risk.
Keywords: DATA PROTECTION